Gait ecological assessment in persons with Parkinson’s disease engaged in a synchronized musical rehabilitation program - A. Bourdon; L. Damm; D. Dotov; P. Ihalainen; S. Dalla Bella; B. G. Bardy; V. Cochen De Cock (npj Parkinson's Disease)
Abstract Data on gait parameters during real-life activities and home rehabilitation programs for Persons with Parkinson’s disease (PwPDs) are scarce. Although cueing has been shown to improve their gait in laboratory conditions, few studies have applied this technique in at-home rehabilitation programs. Our study aimed to explore the use of a real-time synchronized beat-step music program for at-home rehabilitation. We conducted a 1-month outdoor gait rehabilitation program called BeatPark (30 min/day, 5 days/week), with 25 PwPDs, using real-time synchronized, cued, music, and measurements through the BeatMove application. We demonstrated that real-world walking with BeatMove exhibited improved gait parameters both within and across sessions. These improvements were further confirmed by the Six-Minute Walk Test conducted in silence in the laboratory before and after the program. Measures in real life are unique tools to enhance rehabilitation programs. Future research incorporating a control group will be essential to fully validate these encouraging findings.